2008
DOI: 10.1080/14622200701705035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cigarette smoke exposure on the growth of Streptococcus mutans and Streptococcus sanguis: An in vitro study

Abstract: The aim of the present study was to determine the effect of cigarette smoke on the growth of Streptococcus mutans and Streptococcus sanguis. The standard strains of S. mutans (ATCC 25175) and S. sanguis (ATCC 10556) were cultured on blood agar and incubated for 48 hr in three main environments: atmospheric air, carbon dioxide, and cigarette smoke. Kent gold 1(nicotine: 0.1 mg, tar: 1 mg), Kent lights (nicotine: 0.8 mg, tar: 9 mg) and Bahman (nicotine: 1 mg, tar: 13 mg) were the brands used in the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 17 publications
3
40
0
2
Order By: Relevance
“…Zonuz and colleagues studied the growth of S. mutans (ATCC 25175) and S. sanguis (ATCC 10556) on atmospheric air, CO 2 , and cigarette smoke (Kent gold, Kent lights, and Bahman) and the results of this study indicated significantly increased the growth of S. mutans in cigarette smoke and CO 2 with the greatest impact of Bahman. They have also reported mutans/sanguis ratio of 1, 0.84, and 0.98 in Kent gold, Kent lights, and Bahman, respectively (19). The results of this study is similar to the present study, regarding greater growth of streptococcus in cigarette smoke, and CO 2 , however, the growth of S. mutans was greater in their study than S. sanguis, while in the present study, it was vice versa.…”
Section: Discussionsupporting
confidence: 36%
See 1 more Smart Citation
“…Zonuz and colleagues studied the growth of S. mutans (ATCC 25175) and S. sanguis (ATCC 10556) on atmospheric air, CO 2 , and cigarette smoke (Kent gold, Kent lights, and Bahman) and the results of this study indicated significantly increased the growth of S. mutans in cigarette smoke and CO 2 with the greatest impact of Bahman. They have also reported mutans/sanguis ratio of 1, 0.84, and 0.98 in Kent gold, Kent lights, and Bahman, respectively (19). The results of this study is similar to the present study, regarding greater growth of streptococcus in cigarette smoke, and CO 2 , however, the growth of S. mutans was greater in their study than S. sanguis, while in the present study, it was vice versa.…”
Section: Discussionsupporting
confidence: 36%
“…Considering the increased risk of periodontal diseases, and the major role of S. mutans and sanguis in oral dis- eases, studies have investigated the effect of smoking on the growth of these two bacteria (19).…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoke condensate (CSC) has been reported to elicit morphological and transcriptional changes that suggest epithelialto-mesenchymal transition (EMT) in cultured bronchial epithelial cells (Polk 2012). Zonuz et al (2008) reported that the growth of Streptococcus mutans and Streptococcus sanguis is accelerated in the vicinity of CSC. CSC has also been reported to interfere with the adhesion and biofilm formation in contact with Streptococcus mutans and Candida albicans cells (Baboni et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the nicotine in tobacco smoke enhances the growth of S. mutans (15) . Smokers have increased amounts of S. mutans in the oral cavity when compared with non-smokers.…”
Section: Increases Bacteriamentioning
confidence: 99%